Lateral rectus palsy as the first presentation of Kikuchi Fujimoto’s disease - M. S. N. Padmasiri; M. I. Mujaheith (Sri Lanka College of Internal Medicine, 2024)
Kikuchi Fujimoto's Disease (KFD) or histiocytic necrotising lymphadenitis is recognised as a disease with a benign and indolent course. The common clinical symptoms of KFD include fever, headache, arthralgia and cervical lymphadenopathy. The diagnosis is based on clinical grounds and histological findings of lymph node biopsy. Kikuchi disease presenting with neurological manifestations is seldom seen. Out of all reported neurological manifestations, aseptic meningitis, brainstem encephalitis and cerebellar ataxia are common. We report a case of a 16 year old girl presenting with right sided lateral rectus palsy as the first presentation of KFD.